Alteration of Gut Microbiota in Individuals at High-Risk for Rheumatoid Arthritis Associated With Disturbed Metabolome and the Initiation of Arthritis Through the Triggering of Mucosal Immunity Imbalance - Luo, Yubin; Tong, Yanli; Wu, Liang; Niu, Haitao; Li, Yanhong; Su, Lin Chong; Wu, Yuxi; Bozec, Aline; Zaiss, Mario; Qing, Pingying; Zhao, Hua; Tan, Chunyu; et al. (Arthritis and Rheumatology, 2023)
Objective: In this study, we aimed to decipher the gut microbiome (GM) and serum metabolic characteristic of individuals at high risk for rheumatoid arthritis (RA) and to investigate the causative effect of GM on the mucosal immune system and its involvement in the pathogenesis of arthritis. Methods: Fecal samples were collected from 38 healthy individuals and 53 high-risk RA individuals with anti–citrullinated protein antibody (ACPA) positivity (Pre-RA), 12 of 53 Pre-RA individuals developed RA within 5 years of follow-up. The differences in intestinal microbial composition between the healthy controls and Pre-RA individuals or among Pre-RA subgroups were identified by 16S ribosomal RNA sequencing. The serum metabolite profile and its correlation with GM were also explored. Moreover, antibiotic-pretreated mice that received GM from the healthy control or Pre-RA groups were then evaluated for intestinal permeability, inflammatory cytokines, and immune cell populations. Collagen-induced arthritis (CIA) was also applied to test the effect of fecal microbiota transplantation (FMT) from Pre-RA individuals on arthritis severity in mice. Results: Stool microbial diversity was lower in Pre-RA individuals than in healthy controls. The bacterial community structure and function significantly differed between healthy controls and Pre-RA individuals. Although there were differences to some extent in the bacterial abundance among the Pre-RA subgroups, no robust functional differences were observed. The metabolites in the serum of the Pre-RA group were dramatically different from those in the healthy controls group, with KEGG pathway enrichment of amino acid and lipid metabolism. Moreover, intestinal bacteria from the Pre-RA group increased intestinal permeability in FMT mice and zonula occludens-1 expression in the small intestine and Caco-2 cells. Moreover, Th17 cells in the mesenteric lymph nodes and Peyer's patches were also increased in mice receiving Pre-RA feces compared to healthy controls. The changes in intestinal permeability and Th17-cell activation prior to arthritis induction enhanced CIA severity in PreRA-FMT mice compared with HC-FMT mice. Conclusion: Gut microbial dysbiosis and metabolome alterations already occur in individuals at high risk for RA. FMT from preclinical individuals triggers intestinal barrier dysfunction and changes mucosal immunity, further contributing to the development of arthritis.
CRIS-Team Scopus Importer:2023-09-29